Does market access drive trade growth? Evidence from China - Jianxin Mao; Chaoran Pan; Luoxin Wang; Ming Liu (PLoS ONE, 2025)
Against the backdrop of a turbulent global trade environment, high-quality development of foreign trade is an important driving force for the recovery and sustainable development of both China and other economies worldwide. This study investigates the influence of market access on the high-quality development of foreign trade, using panel data from 260 Chinese cities from 2014 to 2023. A fixed-effects model explores the nonlinear relationship, the transmission mechanisms of industrial structure advancement and economic agglomeration, and the moderating effect of industrial rationalization. The results reveal a significant positive U-shaped relationship: at low levels, market access improvements suppress trade quality, but beyond a critical threshold, the effect turns strongly positive. Mechanism analysis confirms that industrial structure advancement and economic agglomeration are key pathways through which market access promotes trade quality. Moreover, industrial rationalization exerts a moderating effect that reinforces the impact of market access. These findings enrich the understanding of foreign trade upgrading spatial drivers and highlight the nonlinear dynamics of market access in shaping trade quality.